2012
DOI: 10.1063/1.3695376
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation and enhanced magnetoresistance in the strained epitaxial La0.625Ca0.375MnO3 (001) films

Abstract: Strain effect caused by substrates on phase separation and transport properties in Pr0.7(Ca0.8Sr0.2)0.3MnO3 thin films J. Appl. Phys. 111, 07D721 (2012); 10.1063/1.3678297 Phase separation and persistent magnetic memory effect in La 0.625 Ca 0.375 MnO 3 and La 0.375 Pr 0.25 Ca 0.375 MnO 3 films La 0.625 Ca 0.375 MnO 3 films have been epitaxially grown on the (LaAlO 3 ) 0.3 (Sr 2 AlTaO 6 ) 0.35 (001) substrates at different oxygen pressures and show varying tetragonal distortion. Results indicate a tendency tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…LaAlO 3 is a great example with almost no diffusion at conventional deposition temperatures, and the LaAlO 3 film has been successfully deposited on Si, MgO, and SrTiO 3 substrates. In addition, the LaAlO 3 film is a potential buffer layer for the growth of various perovskite films. Furthermore, because of the low conduction band offset, LaAlO 3 can be utilized as a charge storage layer in the fields of charge trap flash devices . In particular, LaAlO 3 is a powerful candidate for high- k materials in advanced Si-based complementary metal-oxide-semiconductor (CMOS) devices , because of its own unique features. , …”
Section: Introductionmentioning
confidence: 99%
“…LaAlO 3 is a great example with almost no diffusion at conventional deposition temperatures, and the LaAlO 3 film has been successfully deposited on Si, MgO, and SrTiO 3 substrates. In addition, the LaAlO 3 film is a potential buffer layer for the growth of various perovskite films. Furthermore, because of the low conduction band offset, LaAlO 3 can be utilized as a charge storage layer in the fields of charge trap flash devices . In particular, LaAlO 3 is a powerful candidate for high- k materials in advanced Si-based complementary metal-oxide-semiconductor (CMOS) devices , because of its own unique features. , …”
Section: Introductionmentioning
confidence: 99%
“…CMR effect in epitaxial La 0.625 Ca 0.375 MnO 3 films strongly increases with decrease of film thickness and strain relaxation degree, confirming the important role of lattice strain in determining physical properties. 9 More recently, three groups, [9][10][11] all demonstrated that the electromagnetic transport behavior of CMR manganite multilayers has been attributed to presence of lattice strain and disorder in epitaxial films. These results illustrated the importance of lattice strain and interfaces in determining physical properties of the oxide multilayers.…”
mentioning
confidence: 99%